Manajemen Umroh Pada PT. Putra Duta Wisata Palembang - Rizki, Cindy; Hasmawati, Fifi (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This thesis is entitled "Umrah Management at PT. Putra Duta Wisata Palembang" This study aims to find out about the implementation of Umrah management at PT. Putra Duta Wisata. This study uses a descriptive qualitative approach method with data collection through interviews, observation and documentation. The results of this study generally show that PT. Putra Duta Wisata Palembang applies Umrah Management which has been implemented quite well through several processes which are management functions from planning which include internal meetings, selecting hotels and airlines determining package prices, organizing namely arranging tasks and responsibilities in managing Umrah worship activities to be carried out, implementing Umrah worship and supervision carried out from departure to return this has a positive impact on the congregation towards satisfaction and smoothness of Umrah worship, so that Umrah management activities can be implemented and fulfill the wishes of the congregation and attract the interest of the congregation to continue to trust this travel agency and also this company is expected to continue to improve the management of the quality of service provided to Umrah pilgrims at PT. Putra Duta Wisata